The Effect of RAFT Strategy on Students’ Writing Ability - Prihatin Nurhidayati; Heny Friantary; Hengki Satrisno; Feny Martina (Jadila: Journal of Development and Innovation in Language and Literature Education, 2022)
Language skills must be owned by students. Therefore, the teacher's role is very important in the learning process because it must be able to provide strategic, innovative, and interesting methods, strategies, and learning media so that students are able to master the four language skills in Indonesian lessons, meaning that students must master these four skills in a balanced way. However, in reality, writing skills are still less favored by students, this is due to the number of students who have difficulty expressing ideas, feelings, and thoughts through writing. So that learning to write is more difficult than the three competencies in other language learning. The purpose of this study was to determine the effect of the RAFT strategy on the development of descriptive text writing skills for students of class X IPA1 SMA Negeri 2 Seluma. The type of research used is quantitative research. The sample of this study was 34 people. The instruments used are test sheets and documentation. The results obtained from this study, it is known that the hypothesis test was carried out, it was obtained that the value of Fcount> Ftable i.e. = 0.48 > 0.39, thus the hypothesis Ha was accepted, which means that the implementation of the RAFT strategy can improve the development of text writing skills. description of students of class X IPA1 SMA Negeri 2 Seluma. The implementation of the influence test in the results of this study found that the raft learning strategy on the development of writing skills in class X IPA1 SMA Negeri 2 Seluma, with the results of data management from the research conducted, it is known that there is a positive influence between RAFT strategy (X) on the development of descriptive text writing skills (Y).